Eksistensi Nilai Sosial Budaya Ndeu Paki Oi Mbaru Pada Masyarakat Donggo Kabupaten Bima - Sumitro, Sumitro; Oruh, Shermina; Agustang, Andi (Lembaga Penelitian dan Pendidikan Mandala, 2021)
This study aims to determine the existence of the social value of the ndeu paki oi mbaru community of donggo, bima regency. this research is a qualitative descriptive research that aims to explain a situation or reality carefully and in accordance with the circumstances in society. the subjects in this research can be selected by purposive sampling, namely by determining the informants who have competence and know a problem to be studied. the number of informants in this study were 20 people. the informants who were targeted in this study were community members who were married, those who were not married, and those who were about to get married. an urgent problem in this research is the fading identity of the paki oi mbaru ceremony, currently in the donggo traditional wedding ceremony, the donggo community has rarely carried out the ceremony before the marriage contract. from this phenomenon, researchers will study the existence of the paki oi mbaru ceremony in the donggo community, bima regency. The results showed that the paki oi mbaru ceremony was rarely practiced by the donggo community, bima regency. the causes of the disappearance of the ndeu paki oi mbaru ceremony in the donggo community are as follows; 1. the internal factor of the community itself because it does not attach importance to tradition and culture from generation to generation and there is an assumption that when carrying out traditions it only costs a lot of money and wastes a lot of time. 2. external factors, namely contact with other cultures, such as cultural acculturation, the influence of mass media and modernization. The conclusion of this study is that the ndeu paki oi mbaru ceremony is no longer carried out by the donggo community in general, except that only certain people still carry it out and even then only a few of the existing donggo community.